A University EFL Teacher’s Strategies in Solving the Teaching Pronunciation Problems - Bella Mulia Grandyna (Universitas Muhammadiyah Yogyakarta, 2018)
This study aimed to deal with a university English as a Foreign Language (EFL) teacher’s experience in teaching pronunciation, particularly on the problems faced by teacher and the strategies used in solving the problems in teaching pronunciation. To achieve the objectives, two interviews was done to Lily, an English teacher who had been given responsibility to teach pronunciation in a private university of Yogyakarta. The collected data was obtained from narrative inquiry design in qualitative method. The findings of the study discovered that familiarize the different sounds, lack of time and problems from students’ side were all the problems faced by Lily. Moreover, increasing teaching quality, introducing pronunciation rules, and using various teaching techniques and classroom activities became the strategies to solve teaching pronunciation problems.